Model Kompetensi Kepemimpinan Kepala Ruang Meningkatkan Motivasi dan Kinerja Perawat Pelaksana - Putu Widhi Sudariani; Budi Utomo; Rizki Fitryasari (Universitas Airlangga, 2016)
Introduction: Leadership competencies are unsuitable that given the leadership to employees, can decrease the motivation, performance and ultimately job satisfaction. This research was conducted to develop a leadership competency model as an effort to improve the motivation and performance of nurses so as to improve health services. Methods: This research have two phase, phase one is analytic observational with 140 sample, analysis data with partial least square (PLS), formulation of strategic issues using focus group discussion (FGD), then make a modul with some expertise. Phase two is quasy experimental with 32 sample divided into two group, there are treatment group and control group. Analysis data in phase two with wilcoxon signed rank test and mann whitney. Result: Phase one there is influence of internal factors (knowledge, skills, and values) to the leadership competencies (t = 3.728> 1.96), there is influence of external factors (cultural organizations) to the leadership competencies (t = 2.257> 1.96), competence leadership influence motivation (t = 3,432> 1,96), leadership competencies influence to performance (t = 2.878> 1.96). The second phase, calculation with Wilcoxon signed rank test showed there is difference motivation in treatment group pre-test and post-test, Mann-Whitney test showed there is influence of development leadership competency model to the motivation of nurses. Test Wilcoxon signed rank test for performance of nurses showed there is difference between pre-test and post-test, Mann-Whitney test was obtained there is influence development of leadership competency model to the performance of nurses. Discussion: Development of leadership competency model can increase the motivation and performance of nurses.